If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 3) = -2(5x + -6) Reorder the terms: 3(3 + 2x) = -2(5x + -6) (3 * 3 + 2x * 3) = -2(5x + -6) (9 + 6x) = -2(5x + -6) Reorder the terms: 9 + 6x = -2(-6 + 5x) 9 + 6x = (-6 * -2 + 5x * -2) 9 + 6x = (12 + -10x) Solving 9 + 6x = 12 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 9 + 6x + 10x = 12 + -10x + 10x Combine like terms: 6x + 10x = 16x 9 + 16x = 12 + -10x + 10x Combine like terms: -10x + 10x = 0 9 + 16x = 12 + 0 9 + 16x = 12 Add '-9' to each side of the equation. 9 + -9 + 16x = 12 + -9 Combine like terms: 9 + -9 = 0 0 + 16x = 12 + -9 16x = 12 + -9 Combine like terms: 12 + -9 = 3 16x = 3 Divide each side by '16'. x = 0.1875 Simplifying x = 0.1875
| (x2)^2/x^2x | | 25n^2+15n+2=0 | | 2n=40n+3 | | 16=x^2+2x | | x+(0.14)=4500 | | y=4x^2+4x-8 | | 5x(2-7x)= | | 3x-5=6(x-3) | | 2(x+4)-(5-2x)=5 | | 7n(-3+5n)+2= | | 5x^2-35x-10=0 | | 4-5x=9+8x | | 80-y=20 | | 3/8=rt2/3 | | 8(2x+3)=4 | | -4(5x-8)= | | 12=7x-72 | | 50-5(2x+4)=20x-100 | | .5t+.1=3-t | | -18z-3=-3z-2 | | 1/f=1/2+1/4 | | 1/2•1/3 | | 1+2(y+4)= | | -1d=4d | | y/8-2=6 | | 2x-3y=125 | | x^2+8xy+16y^3=0 | | 12/5÷60 | | -18=-7w+12 | | -1/1/4= | | 8y+4+4y+8=15y-8 | | 81x^2-12=0 |